IMPLEMENTATION OF THE SUPERVISION FUNCTION OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL OF REGIONAL REGULATIONS IN SURABAYA CITY - Dewi Agustin Dwiyanti; Catur Wido Haruni; Fitria Esfandiari (Universitas Muhammadiyah Tangerang, 2021)
The Regional People's Representative Council (DPRD) as an element in administering the Regional Government which is positioned as an equal partner with the Regional Government has the main function of controlling the running of the Regional Government to realize good governance. So that the DPRD's oversight function of the implementation of Regional Regulations which is the main activity of DPRD in controlling the running of Regional Government will be the focus of research. The problem in this paper is knowing and analyzing the form of DPRD supervision on the implementation of Regional Regulations in the City of Surabaya and the follow-up of the supervisory function on the implementation of Regional Regulations in the City of Surabaya. In addition, it also analyzes the obstacles faced in carrying out this supervisory function. The method used is a sociological juridical approach, which is a study of the real situation of the community or the real situation in the field with the intent and purpose of finding facts. The results showed that the form of DPRD supervision of the implementation of Regional Regulations in the City of Surabaya was carried out through DPRD organs by means of preventive supervision and also repressive supervision. Furthermore, follow-up supervision is carried out by providing recommendations to the Regional Government to provide suggestions and to make improvements. The obstacles faced by the DPRD in carrying out its supervisory function are internal and external factors. Finally, carrying out the supervisory function of the Surabaya City DPRD has not been carried out optimally so that the implementation of the supervisory function needs regulations that regulate and also regulations related to the formal education standards for the recruitment of DPRD members.Keywords : Implementation, Control Function of Regional People’s Representative